A Unified Open-Source Metabase Design for Hydro-meteorological Data Descriptive Analysis - Lyronis, Antonios; Varouchakis, Emmanouil A.; Anyfanti, Ioanna; Karatzas, George P. (Environmental processes, 2025)
Various operators run meteorological stations in the region of Crete, each of which collects important climate data. However, this fragmentation leads to difficulties in integrating and analyzing the data throughout the region. The present work describes the creation of a unified, open-source SQL database for the management of hydro-meteorological data from a large number of monitoring stations in the region of Crete and the development of an infrastructure with a user interface. The characteristics of originality and innovation of the idea lie in the integration and collection of a variety of meteorological and hydrological data from a multitude of independent meteorological and hydrological stations in the region of Crete and their dissemination to the wider scientific community through a multi-user access environment. The integration of the data into a single MySQL database and the user-friendly interaction with the database through Metabase add value to the collected data compared to storage in isolated individual databases or files. The customizable visual representation of the data, the ability to create personalized queries without requiring prior knowledge of database programming, and the possibility of automatic data entry (either via the accredited bodies’ websites or via files in specific formats) are additional original features. By providing clear visual representations of this data, the platform would improve decision-making in critical areas such as flood risk management, drought mitigation and sustainable water resource planning. The introduction of such a consolidated system would simplify hydrological studies, encourage collaboration between data providers and facilitate more informed, data-driven policy making. Highlights A Unified open-source platform was created for the management of meteorological data. The platform incorporates tools for statistical analysis and data visualization. Statistical and graphical tools enable users to track data for risk management. Monthly open-source data aggregation ensures up-to-date information. The platform encourages contributions from the public and private sector.